Everyday chemical : The young scientist investigates. - Jennings, Terry (New york : Toronto : Oxford university press, 1989)
An introduction to the many kinds of chemicals, describing some of their uses to man. Includes study questions, activities and experiments.
includes bibliographical references.
Keywords: chemical